The Development Of Guidelines For The Arrangement Of Character-Based English Language Lesson Plan For The Teachers Of Junior Secondary Schools In Surakarta City: A Preliminary Study - Joko Nurkamto (Bandar Lampung University (UBL), 2013)
The final objective of this research is to produce guidelines for character-based English language lesson plan for the teachers of Junior Secondary Schools in Surakarta city.This research employed Research and Development (R&D) method comprising three phases, namely: exploration phase (Year 2012), model development phase (tahun 2013), andmodel evaluation phase (Year 2014). In the first phase, the existence and quality of the prevailing guidelines for the lesson plan arrangement were studied as a basis for drafting a prototype of the guidelines for the arrangement of character-based English language lesson plan.As many as 56 English teachers of Junior Secondary Schools in Surakarta city were involved in the research.The results of the research show that (1) the guidelines for the lesson plan arrangement made by the government are designed for all subject matters and are general in nature; (2) the lesson plans arranged by the teachers of Junior Secondary Schools in Surakarta city still contain many weaknesses; and (3) special or specific guidelines for the arrangement of character-based English language lesson plan are required for the teachers of Junior Secondary Schools in Surakarta city.